2021
DOI: 10.3390/antibiotics10030226
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Nosocomial Pneumonia Caused by Colistin-Resistant Escherichia coli in Patients Admitted to Chest Intensive Care Unit

Abstract: (1) Background: Colistin is a last-resort antibiotic used in treating multidrug-resistant Gram-negative infections. The growing emergence of colistin resistance in Escherichia coli (E. coli) represents a serious health threat, particularly to intensive care unit (ICU) patients. (2) Methods: In this work, we investigated the emergence of colistin resistance in 140 nosocomial E. coli isolated from patients with pneumonia and admitted to the chest ICU over 36 months. Virulence and resistance-related genes and E. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 83 publications
1
5
0
Order By: Relevance
“…The only drugs that exhibited fairly low overall resistance rates were linezolid and colistin. Linezolid resistance across Europe and worldwide remains low [23,24], but colistin-resistant HAIs in ICUs are becoming a concern [25,26]. Colistin plays a crucial role in treatment of MDR infections, and efforts toward determining colistin resistance on a larger scale are ongoing [27].…”
Section: Discussionmentioning
confidence: 99%
“…The only drugs that exhibited fairly low overall resistance rates were linezolid and colistin. Linezolid resistance across Europe and worldwide remains low [23,24], but colistin-resistant HAIs in ICUs are becoming a concern [25,26]. Colistin plays a crucial role in treatment of MDR infections, and efforts toward determining colistin resistance on a larger scale are ongoing [27].…”
Section: Discussionmentioning
confidence: 99%
“…The cationic portion of the zwitterionic groups interacts with negatively charged bacterial cell membranes to result in the effect of cell lysis [ 52 , 53 , 54 ]. Gram-negative bacterium E. coli and Gram-positive bacterium S. aureus are common and representative infection strains [ 55 ], which are used to evaluate the antibacterial effect of the NR/GO and NR/GO-PSBMA films. Antibacterial activity was determined through the use of the disc diffusion assay of NR/GO films and NR/GO-PSBMA films ( Figure 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…The first report of mcr-1 from a clinical isolate in Egypt was provided in 2016 by Elnahriry et al (2016) . Then, different studies reported the presence of mcr-1 among E. coli clinical isolates in Egypt, including Anan et al (2021) , who found only four (7.5%) E. coli harboring mcr-1 among colistin-resistant isolates, and El-Mokhtar et al (2021) who reported that all their studied E. coli isolates resistant to colistin carried mcr-1 . Moreover, another study reported the presence of mcr-1 in one E. coli and one K. pneumoniae isolate among their 450 enterobacterial isolates ( Zafer et al 2019 ).…”
Section: Discussionmentioning
confidence: 99%